1995
DOI: 10.1096/fasebj.9.1.7821748
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular signaling upon complexation

Abstract: Crystal habits can be used as indicators of conformational changes in their constituent proteins. As in the conversion of unliganded hemoglobin to the oxygenated form, the addition of a small hapten to a suspension of platy crystals of an unliganded Fab (NC6.8) results in the immediate disintegration of the plates and their replacement with prisms of the ligand-protein complex. Examination of the native and liganded forms by X-ray crystallography reveals that the space groups and protein structures are differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
1
18
0
1
Order By: Relevance
“…The density related to the variable domains of the Fab fragments was almost as strong as the density of the glycoprotein shell, indicating ∼90% occupancy of the 120 binding sites (87% for X1, 93% for X2). The density related to the constant regions of Fab CR4354 is only about 0.7-fold as strong as the variable region, suggesting flexibility of the elbow angle between variable and constant domains, as often observed with antibody structures (23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 55%
“…The density related to the variable domains of the Fab fragments was almost as strong as the density of the glycoprotein shell, indicating ∼90% occupancy of the 120 binding sites (87% for X1, 93% for X2). The density related to the constant regions of Fab CR4354 is only about 0.7-fold as strong as the variable region, suggesting flexibility of the elbow angle between variable and constant domains, as often observed with antibody structures (23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 55%
“…Indeed, a conformational change in the elbow angle of Ϸ40°relative to that in the crystal structure of the Fab E16ϩDIII complex (Fig. 4) shows flexibility, as is often found in antibody structures (30)(31)(32)(33). Presumably, the very similar elbow angles in the Fab molecules bound to the independent binding sites DIII-B and DIII-C in the cryo-EM structure represent the lowest energy conformation, whereas the x-ray structure may have a slightly higher energy to achieve better crystal packing.…”
Section: W Est Nile Virus (Wnv) Causes a Febrile Illness In Humansmentioning
confidence: 64%
“…Amino acid substitution experiments have shown that disrupting the ball-and-socket joint can markedly decrease signaling while having only a minimal effect on antigen binding (24). Antigen binding is thought to cause the elbow to bend, affecting the initiation of signaling (25,26). However, precisely how bending relates to signaling remains unclear; indeed, the mechanism of signaling itself remains uncertain, with competing proposals disagreeing over whether aggregation or disaggregation of BCRs at the B-cell surface is required (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%